2020
DOI: 10.4314/ijbcs.v13i7.14
|View full text |Cite
|
Sign up to set email alerts
|

Influence du génotype et du nombre de feuilles sur la croissance en pépinière des boutures du colatier (<i>Cola nitida</i> [Vent.] Schott et Endlicher.)

Abstract: Malgré son importance socioéconomique, la production ivoirienne de noix de cola est confrontée à plusieurs difficultés. Le manque de techniques culturales éprouvées constitue une des contraintes pour la domestication et la culture du colatier. Il est donc nécessaire de mettre au point des techniques adaptées à l’espèce cultivée. L’objectif de cette étude est d’optimiser la méthode de bouturage sous tunnel du colatier (Cola nitida), face aux inconvénients de la multiplication générative. Le dispositif expérimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…These findings line up with those of Essola et al (2017) who reported a mean survival of 45 and 52.57% for cuttings of SNK16 and T79/501 respectively. Similarly, Kamga et al (2018) obtained a 60% survival rate with hybrid cocoa cuttings, whereas Séry et al (2019) reported a 41.7% survival rate with Cola nitida cuttings. From the 4320 grafted plants established in this experiment, 4039 grafted plants were recorded after data cleaning and 3285 (81%) survived at the first week of measurement and then decreased to 1794 (44,4%) at the fourth week data collection.…”
Section: Effect Of Clone On Survival Rate Measured Weekly For Four We...mentioning
confidence: 97%
“…These findings line up with those of Essola et al (2017) who reported a mean survival of 45 and 52.57% for cuttings of SNK16 and T79/501 respectively. Similarly, Kamga et al (2018) obtained a 60% survival rate with hybrid cocoa cuttings, whereas Séry et al (2019) reported a 41.7% survival rate with Cola nitida cuttings. From the 4320 grafted plants established in this experiment, 4039 grafted plants were recorded after data cleaning and 3285 (81%) survived at the first week of measurement and then decreased to 1794 (44,4%) at the fourth week data collection.…”
Section: Effect Of Clone On Survival Rate Measured Weekly For Four We...mentioning
confidence: 97%
“…These factors are, among others, the genotype, the number of leaves, the type of substrate, the length of the cuttings, the type of branch, the number and position of nodes as well as the concentration of plant hormones . In addition, the survival and rooting rates obtained from kola tree cuttings were relatively low (Sery et al, 2019). It is therefore necessary to propose methods to accelerate the growth and root development of kola tree cuttings.…”
Section: Work Carried Out On the Generative Reproduction Ofmentioning
confidence: 99%
“…This genus is well-known for its medicinal benefits as well as for its many uses throughout Africa (Ouattara et al, 2018;Sery et al, 2019). It contains several species, but only two are cultivated for their scientific and economic values.…”
Section: Introductionmentioning
confidence: 99%